Entrepreneurship Based on Culture and Local Wisdom: Building Sustainable Business from Tradition - Rifqiansyah; Hasrul wijaya (Cendekiawan Indonesia Timur, 2025)
Entrepreneurship based on culture and local wisdom plays a crucial role in fostering sustainable business models that preserve traditions while contributing to economic growth. This study explores how traditional knowledge, cultural heritage, and local practices shape entrepreneurial initiatives that balance profitability with social and environmental sustainability. Using a qualitative approach, this paper examines successful cases of culture-based entrepreneurship in Indonesia, highlighting strategies for integrating tradition into contemporary business models. The findings indicate that businesses leveraging cultural assets—such as traditional crafts, culinary heritage, and indigenous knowledge—demonstrate unique market positioning, strong community engagement, and resilience against economic fluctuations. However, entrepreneurs face challenges, including market adaptation, limited access to modern technology, and competition with mass-produced alternatives. Government policies, local support systems, and digital transformation play a significant role in sustaining these businesses. This study emphasizes that cultural entrepreneurship not only preserves intangible heritage but also fosters economic empowerment and sustainable livelihoods. It suggests that fostering collaboration among policymakers, educational institutions, and entrepreneurs is essential for enhancing the scalability of culture-based businesses. By embracing innovation while respecting tradition, entrepreneurs can create sustainable ventures that maintain cultural authenticity while meeting contemporary market demands.